The Influence of Principal Leadership and Teacher Performance on Student Achievement: A Survey Study in Indonesia - Ahmadi Ahmadi; Meilia Rosani; Mulyadi Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the influence of principal’s leadership and teacher’s performance on student’s achievement at SMAN 2 Muara Sugihan. The method used is a survey with a questionnaire involving 30 teachers as respondents. The data obtained were analyzed using descriptive and inferential statistics, including validity, reliability, and multiple regression tests. The results of the study indicate that principal’s leadership has a positive and significant effect on student’s achievement, with a t-test of 12.862 and a significance of 0.005. In addition, teacher’s performance also has a positive and significant effect on student’s achievement, with a t-test of 13,268 and a significance of 0.000. Simultaneously, principal’s leadership and teacher’s performance have a significant effect on student’s achievement, with a significance value of 0.008. The coefficient of determination (R²) shows that 80.7% of the variation in student’s achievement can be explained by the two independent variables. This finding confirms the importance of the role of leadership and teacher’s performance in improving student’s achievement, as well as providing recommendations for the development of educational policies in schools.